Study of congenital malformations in newborns: a hospital based prospective study - Patel, Kinjal G.; Chaudhary, Chintu (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital malformations represent a defect in the morphogenesis during fetal life. Since the introduction of primary health care and immunization programme, congenital malformations have emerged as one of the commonest cause of perinatal mortality. The objective was to study the incidence, systemic distribution, various maternal risk factors and immediate outcome of congenital malformations in hospital delivered neonates. Methods: This study was conducted at a tertiary care hospital for a period of 2 years. All the hospital delivered live neonates and stillbirth babies with congenital malformations are included in this study. Detailed history, examinations and investigations are carried out to identify etiological factors. Their outcome in form of morbidity and mortality are taken up to their hospital stay. Results: Out of 9600 babies with malformations 171(1.88%) having single malformation and 23(0.25%) having multiple malformations. Incidence of malformations was higher in stillbirths (24.25/1000 livebirths) against than in live births (19.96/1000 livebirths). The cardiovascular system was involved in 23.4% of babies, followed by musculoskeletal system (22.3%) then gastrointestinal (15.9%) and genitourinary system (15.4%). Multiple malformations were seen in 11.8% cases. Maternal risk factors associated with malformations were oligohydramnios in 4.12%, previous abortion in 2.5%, eclampsia in 2.5%, polyhydramnios in 1.54%, maternal diabetes in 1.54% and consanguinity in 1.03%. Maximum mortality occurred in babies with gastrointestinal system malformations (56.5%) followed by cardiovascular system malformations (21.7%). Majority of babies with malformations discharged (78.9%) only 11.8% of babies expired and 2.6% of babies left against medical advice (LAMA). Conclusions: Congenital malformations represent one of the causes of neonatal mortality. Stillborn babies have higher incidence of malformations. Antenatal ultrasonography and maternal risk factors has important role to identify malformations. Early detection and timely management required to decrease the mortality.